Australian Reporting from East Timor 1975–1999: Journalists as Agents of Change. (December 2013) - Tapsell, Ross; Eidenfalk, Joakim
<x xml:space="preserve">Abstract</x> This article examines Australian reporting in East Timor from 1975 to 1999, and the changing professional practice of Australian journalists who reported from the region during this time. Research conducted for this article includes testimony from the journalists, and a collating of 3, 456 newspaper articles published in the mainstream Australian press on the East Timor situation between 1998 and 1999. It will show that in addition to new regulations over access to the region, new mobile media technologies pushed journalism in new directions, adding to the ability of the journalist to facilitate instantaneous delivery of news to Australia. These reports filed by Australian journalists from East Timor were crucial in fostering the Australian government's decision to send troops to the region.